2004
DOI: 10.1002/chem.200400080
|View full text |Cite
|
Sign up to set email alerts
|

Generating and Dimerizing the Transient 16‐Electron Phosphinidene Complex [Cp*IrPAr]: A Theoretical and Experimental Study

Abstract: The properties of the 16‐electron phosphinidene complex [CpRIrPR] were investigated experimentally and theoretically. Density functional theory calculations show a preferred bent geometry for the model complex [CpIrPH], in contrast to the linear structure of [CpIrNH]. Dimerization to give [{CpIrPH}2] and ligand addition to afford [Cp(L)IrPH] (L=PH3, CO) were calculated to give compounds that were energetically highly favorable, but which differed from the related imido complexes. Transient 16‐electron pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…[51] Lammertsma and co-workers showed that dehydrohalogenation of primary phosphine complex 48 a with the strong phosphazene base tert-butylimino-tri(pyrrolidino)phosphorane (BTPP, pK b % 26) in the absence of a ligand gave 18-electron complex 57 and one-half equivalent of the dimer [{Cp*IrCl 2 } 2 ] (58, Scheme 17 a). [52] Phosphinidene 57 , as identified by its 31 P NMR spectrum (d = 366 and À126 ppm), and suggests that the first dehydrohalogenation is faster than the second one. The reaction appears to be sensitive to the size of the substituent on phosphorus, as the smaller Mes group gave the intermediate dimetallacycle 61, resulting from dimerization of [Cp*(Cl)Ir = P(H)Mes], and subsequently on dehydrohalogenation dimer 62 (Scheme 17 c).…”
Section: Reactive 16-electron Intermediatesmentioning
confidence: 98%
“…[51] Lammertsma and co-workers showed that dehydrohalogenation of primary phosphine complex 48 a with the strong phosphazene base tert-butylimino-tri(pyrrolidino)phosphorane (BTPP, pK b % 26) in the absence of a ligand gave 18-electron complex 57 and one-half equivalent of the dimer [{Cp*IrCl 2 } 2 ] (58, Scheme 17 a). [52] Phosphinidene 57 , as identified by its 31 P NMR spectrum (d = 366 and À126 ppm), and suggests that the first dehydrohalogenation is faster than the second one. The reaction appears to be sensitive to the size of the substituent on phosphorus, as the smaller Mes group gave the intermediate dimetallacycle 61, resulting from dimerization of [Cp*(Cl)Ir = P(H)Mes], and subsequently on dehydrohalogenation dimer 62 (Scheme 17 c).…”
Section: Reactive 16-electron Intermediatesmentioning
confidence: 98%
“…Lammertsma and co-workers reported the dehydrohalogenation of the mononuclear iridium complexes [IrCl 2 Cp*(PH 2 Ar)] (Ar = Mes, Mes*) using the strong phosphazene base BTPP (tert-butylimino-tri(pyrrolidino)phosphorane) (Scheme 17) [43]. The outcome of these reactions, however, was critically dependent on several experimental factors such as the substituent size, temperature and stoichiometry.…”
Section: Dehydrohalogenationmentioning
confidence: 99%
“…Thus, for the bulky PH 2 Mes* phosphine, addition of a two-fold excess of BTPP at room temperature gave the mononuclear phosphinidene [IrCp*(PMes*)(PH 2 Mes*)], while the addition of 1.5 equivalent of base at lower temperature (ca. 200 K) yielded instead the dinuclear phosphinidene/phosphanyl evolves upon addition of further base or on raising the reaction temperature to generate the phosphinidene complex 33, following from a selective C-H bond activation in a putative bis(phosphinidene) intermediate [Ir 2 Cp* 2 (μ-PMes*) 2 ] [43]. In contrast, no phosphinidene complexes could be identified for the Mes-substituted complex, and a double C-H activation product was isolated instead, this suggesting in situ generation of the corresponding bis(phosphinidene) complex which, however, could be neither detected.…”
Section: Dehydrohalogenationmentioning
confidence: 99%
“…Lammertsma und Mitarbeiter berichteten, dass bei der Dehydrohalogenierung des primären Phosphankomplexes 48 a mit der starken Phosphazen‐Base tert ‐Butyliminotri(pyrrolidino)phosphoran (BTPP, p K b ≈26) in Abwesenheit eines Liganden der 18‐Elektronen‐Komplex 57 und das Dimer 1/2 [{Cp*IrCl 2 } 2 ] ( 58 , Schema ) entstehen 52. Es wurde angenommen, dass das Phosphiniden 57 aus der Vorstufe [Cp*IrPMes*] durch Abspaltung von PH 2 Mes* entsteht.…”
Section: Reaktivität Nucleophiler Phosphinidenkomplexeunclassified